WHEAT and MAIZE science, partnerships, outreach led to policies for conservation agriculture and nutrient management in South Asia, mitigating climate change and increasing smallholder income - CGIAR Research Program on Wheat (2021)
WHEAT and MAIZE plus partners' scientific evidence, innovative partnerships and enhanced capacity led to policy changes for large-scale adoption of low-emission, risk-mitigating practices in smallholder wheat systems in South Asia. Adoption of conservation agriculture on 2 million hectares and precision nutrient management on 20 million hectares would potentially benefit around 14 million smallholders, produce around 14 million tons of extra grain, and earn US$ 1.3 billion in additional revenue, while reducing ~3.4 million tons of CO2e each year.